KERJA SAMA ANTARA ORANG TUA DAN SEKOLAH DALAM PENDIDIKAN ANAK MENURUT J.I.G.M. DROST : SUATU KAJIAN FILSAFAT - Ohoiledwarin, Zakarias Sandhy (LOGOS: JURNAL PENDIDIKAN KEAGAMAAN KATOLIK, 2013)
Education is an effort to accompany students to become mature and independent persons. Therefore, education continues for the lifetime and cannot be restricted in certain institutions. Families, communities and schools have their respective roles in carrying out the functions as educators. Today school is regarded as the most responsible for the process of education. Consequently, the education department is regarded as the official institution that contributes to education, whether formal, informal or non-formal. As a result, the role of other educators is not seldom ignored. This paper proposes J.I.G.M. Drost’s concept of education to determine position and the role of any educational institution and to provide the importance of cooperation between educational institutions